Plasma membrane-coated nanoparticles and membrane vesicles to orchestrate multimodal antitumor immunity - Yang Li; Toshiaki Yoshikawa; Yusuke Ito; Satoshi Inoue; Takahiro Nakashima; Noriko Nakamura; Tetsuya Matsukawa; Seiichi Ohta; Yuki Kagoya; Hitomi Kasuya; Mirei Kataoka; Haosong Zhang; et al. (Journal for ImmunoTherapy of Cancer)
Background A number of immunotherapeutic approaches have been developed and are entering the clinic. Bispecific antibodies (BsAbs) are one of these modalities and induce robust efficacy by endogenous T cells in several hematological malignancies. However, most of the treated patients experience only a temporary benefit. Currently available BsAbs provide only anti-CD3 antibody-mediated T-cell stimulation, but not the costimulation or cytokine signaling essential for full T-cell activation. Here, we hypothesized that the simultaneous input of more comprehensive signals would elicit more robust and durable effector T-cell functions.Methods We genetically engineered the leukemia cell line K562 to express BsAbs, costimulatory ligands, cytokines, and blocking antibodies against immune checkpoint molecules on the cell surface, from which we obtained plasma membrane fractions by mechanical homogenization and subsequent isolation steps. Plasma membranes were reconstituted on the poly (lactic-co-glycolic acid) surface to generate membrane-coated nanoparticles (NPs). Alternatively, nano-sized membrane vesicles (MVs) were generated by ultrasonic dispersion of the isolated membranes. The antitumor function of NPs and MVs loaded with various immunomodulatory factors was evaluated in vitro and in vivo.Results Both membrane-coated NPs and MVs induced BsAb-mediated antigen-specific cytotoxic activity in non-specific T cells, with MVs inducing a slightly better response in vivo. Importantly, T-cell activation was elicited only in the presence of target tumor cells, providing a safety advantage for clinical use. NPs and MVs expressing costimulatory molecules (CD80/4-1BBL) and cytokines (interleukin (IL)-7/IL-15) further enhanced effector T-cell function and induced therapeutic efficacy in vivo. In addition, MVs expressing immune checkpoint antibodies and inflammatory cytokines IL-12 and IL-18 induced objective antitumor responses in solid tumor models partly by converting immunosuppressive macrophages to proinflammatory phenotypes and inducing cytotoxic T-cell infiltration into the tumor. Finally, we showed that MVs were also engineered to activate natural killer (NK) cells by loading multiple ligands. MVs loaded with BsAbs, 4-1BBL, IL-15, and IL-21 induced NK-cell cytotoxic activity in an antigen-specific manner.Conclusions We developed antitumor NPs and MVs that efficiently induced antitumor immune responses in vivo by simultaneously delivering multiple immunostimulatory signals to endogenous T cells. This platform enables the delivery of desired combinations of antitumor immune signals into T cells and NK cells.